Пошаговое объяснение:
1) если после слова вираз идет минус:
- 4 (3,6х - 4) - (7 - 2,1х) + 5 (0,3х - 5) = - 14,4х + 16 - 7 + 2,1х + 1,5х - 25 = 10,8х - 16.
При х = 27:
10,8 * 27 - 16 = 275,6
2) если минуса в начале нет:
4 (3,6х - 4) - (7 - 2,1х) + 5 (0,3х - 5) = 14,4х - 16 - 7 + 2,1х + 1,5х - 25 = 18х - 48.
18 * 27 - 48 = 486 - 48 = 438
Пошаговое объяснение:
1) если после слова вираз идет минус:
- 4 (3,6х - 4) - (7 - 2,1х) + 5 (0,3х - 5) = - 14,4х + 16 - 7 + 2,1х + 1,5х - 25 = 10,8х - 16.
При х = 27:
10,8 * 27 - 16 = 275,6
2) если минуса в начале нет:
4 (3,6х - 4) - (7 - 2,1х) + 5 (0,3х - 5) = 14,4х - 16 - 7 + 2,1х + 1,5х - 25 = 18х - 48.
При х = 27:
18 * 27 - 48 = 486 - 48 = 438